VHDL : a starter's guide. - Yalamanchili, Sudhakar, ....- (Upper Saddle River : Pearson, 2005)
For schools that wish to introduce VHDL into their undergraduate computer engineering sequence, VHDL is a complex language that is worthy of a dedicated course; yet this is not a practical option in most institutions. This companion text enables instructors to integrate the basic concepts of VHDL into existing courses. It is designed to develop an intuition and a structured way of thinking about VHDL models without spending a great deal of time on advanced language features. Yalamanchili gives students a thorough grounding in the basic concepts and language of VHDL, and encourages them to apply what they have learned using realistic examples. Concepts are followed by examples and tutorials.
Keywords: VHDL (vhsic hardware description language).